(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Implementation of Good Corporate Governance Principles in the Governance of Perumda Kerta Bali Saguna. Good Corporate Governance (GCG) is a system, pattern, and process in organizing an institution or company in order to achieve the goals of the company concerned. Regional Public Company Kerta Bali Saguna is a renewal and restructuring of the form of a Bali Regional Company in accordance with the Regional Regulation of the Governor of Bali Province in 2022 to maximize the function of Regional Owned Enterprises. With this renewal, Perumda is in the adjustment stage so that the purpose of this research is to find out the extent to which the implementation of GCG principles has been achieved and the achievement of implementing governance through self-assessment scoring at Perumda Kerta Bali Saguna. This study uses qualitative research methods, the source of information comes from primary and secondary data then the results of the data are presented in a descriptive form. Primary data was obtained by means of structured interviews using self-assessment questionnaires and secondary data in the form of supporting documents such as financial reports, annual reports, work plan documents, cooperation documents, and other important documents. Respondents were selected purposively with consideration of important positions that could provide correct, clear and transparent answers. Selected resource persons are the Board of Trustees, Director of Operations, Director of Finance, Operations Manager, and Head of the Trading Industry Business Unit. The data analysis technique used is the interval assessment weight obtained from interviews and supporting documents for each assessment variable. The results of this study prove that the implementation of GCG principles at Perumda Kerta Bali Saguna has implemented good governance, it’s just that it doesn’t have its own specific guidelines and the achievement of the self-assessment score is 72.66 with a fairly good classification.